Parasitoid Chalcidoidea (Insecta: Hymenoptera) Sebagai Agen Pengendalian Hama Secara Biologi Pada Terong (Solanum melongena L.) dan Pare (Momordica charantia L.) - Sofyan, Muhamad Rofik; Ubaidillah, Rosichon (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTThe Parasitics wasp superfamily Chalcidoidea (Insecta : Hymenoptera) potentialas biological control agents for pests of Eggplant (Solanum melongena) and BitterMelon (Momordica charantia). The recent contribution on diversity of parasitics waspChalcidoidea for biological control perspective against the pests of the two economiccrops was discussed, with emphasis on the most significant steps for the selection ofcandidate biological control agents. The survey was carried out in Bogor, West Javausing Malaise traps, Yellow pan traps and a Swept net. The crops are the most economicallyimportant in agriculture not only in West Java but also in Indonesia. Meanwhile the pestcontrol of those two crops has so far been used only by the insecticides and would affectto the health of the production of the crops when the vegetables are consumed freshly. Ofthe 78 species within 8 familes of Chalcidoidea are found in both crops, 7 species can beclassified as potential biological control agents. With the object of biological control ofthese 7 species, a survey was carried out to establish the presence and importance oftheir natural enemies on those crops in Java.Key words : Bitter Melon, Chalcidoidea, Eggplant, Parasitoids, Pest control.